Metabolism and immune responses of striped hamsters to ectoparasite challenges: insights from transcriptomic analysis - Lun, Xinchang; Wang, Yiguan; Zhao, Ning; Yue, Yujuan; Meng, Fengxia; Liu, Qiyong; Song, Xiuping; Liang, Ying; Lu, Liang (Frontiers in Immunology, 2024)
IntroductionThe striped hamster, often parasitized by ectoparasites in nature, is an ideal model for studying host-ectoparasite molecular interactions. Investigating the response to ectoparasites under laboratory conditions helps elucidate the mechanism of host adaptations to ectoparasite pressure.MethodsUsing transcriptome sequencing, we analyzed gene expression in striped hamsters after short-term (3 days) and long-term (28 days) flea (Xenopsylla cheopis) parasitism. Differentially expressed genes (DEGs) were identified and subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Hub genes were pinpointed using protein-protein interaction (PPI) network analysis and the MCODE in Cytoscape. Gene Set Enrichment Analysis (GSEA) was used to further clarify the functional pathways of these hub genes. Validation of DEGs was performed via RT-qPCR. Additionally, the concentrations of reactive oxygen species (ROS), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) were determined using specific enzyme-linked immunosorbent assay (ELISA) detection kits for hamsters.ResultsGO analysis revealed that during early parasitism, hosts primarily responded to the ectoparasites by adjusting the expression of genes related to metabolic functions. As parasitism persisted, the immune response became prominent, activating various immune pathways against ectoparasites. KEGG analysis confirmed the ongoing roles of metabolism and immunity. Notably, the chemical carcinogenesis - reactive oxygen species pathway was upregulated during flea parasitism, with downregulation of hub genes ATP5MC1 and ATP5MC2, highlighting the importance of mitochondrial function in oxidative stress. ELISA findings revealed that on day 3, flea parasitism groups showed elevated ROS expression and reduced SOD and CAT levels compared to the control group. By day 28, only SOD expression showed a significant decrease in both parasitism groups.ConclusionThis study uncovered the dynamic changes in metabolism and immune responses of striped hamsters parasitized by Xenopsylla cheopis. Hosts adjust their physiological and immune states to optimize survival strategies during different ectoparasite stages, enhancing our understanding of host-ectoparasite interactions. This also paves the way for further research into how hosts regulate complex biological processes in response to ectoparasite challenges.